2006
DOI: 10.1111/j.1553-2712.2006.tb00997.x
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Angiography for the Evaluation of Aneurysmal Subarachnoid Hemorrhage

Abstract: In this pilot study, CTA was found to be useful in the detection of cerebral aneurysms and may be useful in the diagnosis of aneurysmal SAH. A larger multicenter study would be useful to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…With the increasing availability of multi-detector CT scanners, some have recommended using CT angiography (CTA) to diagnose SAH (124). Of the 116 patients, 6 (5.1%) had aneurysms (with normal CT but positive CSF findings); these patients would have been identified by the standard work-up.…”
Section: Primary Use Of Ct Angiography For Diagnosis Of Sahmentioning
confidence: 99%
“…With the increasing availability of multi-detector CT scanners, some have recommended using CT angiography (CTA) to diagnose SAH (124). Of the 116 patients, 6 (5.1%) had aneurysms (with normal CT but positive CSF findings); these patients would have been identified by the standard work-up.…”
Section: Primary Use Of Ct Angiography For Diagnosis Of Sahmentioning
confidence: 99%
“…A strategy of CT/CTA has also been suggested and found to be 100% sensitive in one small study (28). Another study showed that this strategy can exclude SAH with a > 99% post-test probability (29).…”
Section: Discussionmentioning
confidence: 96%
“…CTA is often used in first-line aneurysm assessment where is has been shown to be of benefit in aneurysm detection [10][11][12][13][14][15][16][17] and presurgical planning [18]. As a technique it has widespread availability and can perform additional tests such as perfusion studies [19], and postoperative assessments [20].…”
Section: Discussionmentioning
confidence: 99%